2015
DOI: 10.1038/ncomms9003
|View full text |Cite
|
Sign up to set email alerts
|

Gram-scale synthesis of coordination polymer nanodots with renal clearance properties for cancer theranostic applications

Abstract: An ultrasmall hydrodynamic diameter is a critical factor for the renal clearance of nanoparticles from the body within a reasonable timescale. However, the integration of diagnostic and therapeutic components into a single ultrasmall nanoparticle remains challenging. In this study, pH-activated nanodots (termed Fe-CPNDs) composed of coordination polymers were synthesized via a simple and scalable method based on coordination reactions among Fe3+, gallic acid and poly(vinylpyrrolidone) at ambient conditions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(156 citation statements)
references
References 50 publications
5
141
0
Order By: Relevance
“…These results were comparable with previous reports of other MRI contrast agents. 31,39 However, the r 2 :r 1 ratio of GA-Fe@BSA NPs, calculated from the data presented in Figure 4A (r 2 :r 1 =1.06,3), was relatively lower than previously described agents. These results suggested that GA-Fe@ BSA NPs would provide good T 1 -weighted contrast.…”
Section: Mri Of Ga-fe@bsa Npsmentioning
confidence: 56%
See 2 more Smart Citations
“…These results were comparable with previous reports of other MRI contrast agents. 31,39 However, the r 2 :r 1 ratio of GA-Fe@BSA NPs, calculated from the data presented in Figure 4A (r 2 :r 1 =1.06,3), was relatively lower than previously described agents. These results suggested that GA-Fe@ BSA NPs would provide good T 1 -weighted contrast.…”
Section: Mri Of Ga-fe@bsa Npsmentioning
confidence: 56%
“…31,33 The synthesis method is illustrated in Scheme 1 and Figure S1. First, BSA was dissolved in water.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…MRI can give detailed information about abnormal anatomy in a three-dimensional tomographic and real-time manner with high spatial resolution and soft tissue contrast19202122. MRI is normally applied with contrast agents to enhance the signal.…”
mentioning
confidence: 99%
“…Owing to these properties, PNPs have potential uses in the field of biosensors,13 bioimaging,14 and phototherapy 15. In addition, PNPs have been extensively researched for phototheranostic applications 16. However, although some impressive advances have been achieved for PNP‐based phototheranostics, particularly in PA‐imaging‐guided PTT or FL‐imaging‐guided PDT,17 reports on multifunctional and single‐PNP‐based phototheranostic applications are few, and thus, satisfying the “one‐fits‐all” requirement for generalized phototheranostics remains challenging.…”
Section: Introductionmentioning
confidence: 99%